Ethnobotany of the Mountain Regions of Far Eastern Europe-Ural, Northern Caucasus, Turkey, and Iran / Ethnobotany of the Mountain Regions of Central Asia and Altai - A Review - Malik, Zubair A. (Ethnobotany Research and Applications, 2020)
Ethnobotany of the Mountain Regions of Far Eastern Europe-Ural, Northern Caucasus, Turkey, and Iran. Ketevan Batsatsashvili, Zaal Kikvidze, Rainer W. Bussmann (Eds). Springer Nature Switzerland AG 2020. xxix + 1063 pp. Price: € 415.99, ISBN 978-3-030-28939-3. Ethnobotany of the Mountain Regions of Central Asia and Altai. Ketevan Batsatsashvili, Zaal Kikvidze, Rainer W. Bussmann (Eds). Springer Nature Switzerland AG 2020. xxii + 881 pp. Price: € 291.19, ISBN 978-3-030-28946-1. Have you ever imagined how many efforts are required to keep a cultural identity alive? Traditional knowledge, for example, has no doubt gained renewed importance these days, but to make such knowledge available to a wider audience, extensive efforts are required. The books under review are the result of such efforts from their editors who are eminent and renowned ethnobotanists of world. Both the above books are written on the same subject (ethnobotany of the mountain regions), edited by the same editors (Ketevan Batsatsashvili, Zaal Kikvidze and Rainer W. Bussmann), with same presentation style, published by the same publisher (Springer International Publishing) in the same year (2020). So there is a lot of similarity between these books and it will be better to review them together side by side. As already mentioned, these books are a part of book series Ethnobotany of Mountain Regions (ETMORE, https://link.springer.com/bookseries/15885). Eight volumes of this book series have been published so far in the current year (2020).